A postmodern study of politics, language, magic realism and oral tradition in Salman Rushdie’s Midnight’s Children and Haroun and the Sea of Stories - Anjum, Saraf (BRAC Univeristy, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2017.